Diagnosis of infantile subglottic hemangioma: a 10-year experience of 25 cases - Liang, Xiaoben; Xu, Rong; Xu, Hongming; Chen, Jiarui; Li, Xiaoyan (Frontiers in Pediatrics, 2025)
ObjectivesThis study aims to explore the clinical appearances of infantile subglottic hemangioma (SGH) and the diagnostic value of flexible fiberoptic laryngoscopy (FFL) combined with contrast-enhanced CT (CECT).MethodsWe retrospectively analyzed the data of 25 children diagnosed with SGH from January 2012 to January 2022.ResultsFFL showed a smooth, rounded, vascular-appearing submucosal lesion in the subglottic wall, while CECT revealed an enhancing lesion, obscuring the airway lumen. Among the 25 cases (8 males and 17 females; 10 left-sided, 11 right-sided, and 4 middle), the clinical appearances contained stridor (25), respiratory distress (13), three-concave sign (10), barking cough (9), feeding difficulty (8), cyanosis (2), and hoarseness (2). SGH with cutaneous hemangiomas accounted for 24% (6/25). The age at presentation ranged from 1 day to 8 months (median, 33 days), including 96% (24/25) of cases aged <6 months. Moreover, 92% (23/25) of cases had a history of misdiagnosis, 22 respiratory infections, 5 laryngomalacia, 1 laryngeal cyst, and 1 asthma, individually or in combination. Except for one case that died of polygenic abnormality and another case lost to follow-up, the remaining 23 cases were cured after oral propranolol.ConclusionsFor an infant with respiratory symptoms, who has repeated condition or poor effect after routine treatment, SGH should be considered, especially in infants under 6 months old. FFL combined with CECT is recommended to make a definite diagnosis of SGH.